EMC applications for military: Reverberation chamber tests - Choeysakul, Chittawan; Schlagenhaufer, Franz; Rattanakreep, P.; Hall, Peter (Institute of Electrical and Electronics Engineers Inc., 2015)
Electrical and electronic equipment installed on military platforms must have very low electromagnetic emission and good immunity for the whole operational frequency range. Reverberation Chambers (RC) are tools for sensitive emission measurements and immunity tests against strong electromagnetic fields, at a lower cost than other techniques. Method of RC should be suitable for testing Military's electronic devices such as radio or radar system. However, RCs must be large for tests at low frequencies; for example, at 80 MHz are conventional RC must have dimensions up to 7 m by 15 m by 8 m. For military concern, the lowest operation frequency can be as low as 2 MHz (underwater communication can be lower). Conventional RCs can only be used above a certain frequency, the lowest usable frequency (LUF), as they require a minimum mode density (number of modes per frequency interval) in order for the stirrer to perform effectively and alter field distributions. Technique of MIMO RC [1, 2] can make RCs usable down to much lower frequencies; it can mean the dimensions of the chamber can be up to 6 times smaller. However, the composite Q-factor of RCs can be rather low at low frequencies, and this affects the sensitivity, and ultimately usability of an RC. This paper studies the possibility to increase composite Q-factor when RC is used at lower frequencies than conventional method.